Nurse-led interpersonal counselling for depressive symptoms in patients with myocardial infarction - Oranta, Olli (Annales Universitatis Turkuensis D 986, 2011)
The broad interest of this intervention study is in two worldwide remarkable diseases, myocardial infarction and depression. The purpose of the 18-month follow-up study was to evaluate the outcomes of interpersonal counselling implemented by a psychiatric nurse, and to examine the recovery experienced by the patients after myocardial infarction. The interpersonal counseling consisted of a short-term (max 6 sessions) depression-focused intervention modified for myocardial infarction patients. The main principle of interpersonal counselling is that depressive symptoms relate to interpersonal relations. The measured outcomes of the intervention consisted of changes in depressive symptoms and distress, health-related quality of life and the use of health care services. The data consisted of 103 patients with acute myocardial infarction and with sufficient knowledge of Finnish language, and they were randomized into intervention group (n=51) and control group (n=52) with standard care. Depressive symptoms were measured using Beck Depression Inventory, and distress using Symptom Checklist-25. The instrument to measure health-related quality of life was EuroQol-5 Dimensions. All instruments were used at three measurements: in hospital, at 6 months and at 18 months after hospital discharge. The Use of Health Care Services questionnaire was used during the 6- and 18-month period after hospital discharge. In addition, satisfaction with the intervention and with information received from the health-care professional was evaluated during the follow-up. To examine recovery, the patients kept diaries during a 6-month period and they were interviewed at 18 months after myocardial infarction. The number of patients with depressive symptoms decreased significantly more in the intervention group compared with the control group during 18 months of follow-up. Distress decreased significantly more among patients under 60 years in the intervention group than in the control group, but the difference was not significant between the groups. No differences in the changes of health-related quality of life were found between the groups during follow-up. However, in the group of patients under 60 years, the improvement of health-related quality of life in the intervention was significantly better in the intervention group compared with the control group during the follow-up. During the follow-up period, there was even a decline in the use of somatic specialized health care services in the intervention group and among intervention patients who had no other long-term disease. Considering recovery experienced by the patients, main categories including many supporting and inhibiting factors and subcategories were identified: clinical and physical, psychological, social, functional and professional category. No differences between the groups were found in satisfaction with information received from the professionals. The brief and easy-to-learn intervention, with which the patients were satisfied, seems to decrease depressive symptoms after myocardial infarction. Interpersonal counselling seems to be beneficial especially with younger patients. These results justify adopting depression screening and interpersonal counselling as part of routine care after myocardial infarction. The first stage evaluation of the use of health care services is interesting, and calls for more studies. From the perspective of individual patients, recovery after myocardial infarction seems to consist of many supporting and inhibiting factors. This is something that is important to take into account in developing nursing practice. The results indicate a need for further studies in outcomes of interpersonal counselling and recovery experienced by the patients after myocardial infarction. In addition, the results encourage widening the research perspective to nursing administration and educational level.

Tässä tutkimuksessa tarkastellaan laaja-alaisesti kahta, kansainvälisesti merkittävää sairautta: sydäninfarktia ja depressiota. Tutkimus oli 18 kuukauden seurantatutkimus, jossa arvioitiin sairaanhoitajan tekemän interpersonal counselling (interpersoonallinen ohjaus) –intervention tuloksia ja potilaiden kokemuksia sydäninfarktista selviytymisestä. Sydäninfarktipotilaiden masennukseen kohdistunut interventio oli lyhyt, enintään 6 tapaamisen ohjaus, jonka perusidea on tarkastella ihmissuhteiden ja mielialan yhteyttä. Tutkimuksen tulokset koostuivat muutoksista, joita havaittiin potilaiden masennusoireissa, rasittuneisuudessa, terveyteen liittyvässä elämänlaadussa ja terveyspalvelujen käytössä. Aineisto koostui 103:sta akuutin sydäninfarktin saaneesta potilaasta, joilla oli riittävän hyvä suomen kielen taito, ja heidät satunnaistettiin interventioryhmään (n=51) ja kontrolliryhmään (n=52), joka sai normaalihoidon. Depressio-oireita mitattiin Beck Depression Inventory -kyselyllä ja rasittuneisuutta Symptom Checklist-25 –kyselyllä. Terveyteen liittyvää elämänlaatua mitattiin EuroQol-5D -mittarilla. Kaikkia näitä mittareita käytettiin sairaalahoidossa sekä 6 ja 18 kuukautta sairaalahoidon loppumisesta. Terveyspalvelujen käyttö -kyselyä käytettiin 6 ja 18 kuukauden kuluttua sairaalahoidon loppumisesta. Lisäksi seurannan aikana kartoitettiin, kuinka tyytyväisiä potilaat olivat interventioon ja ammattilaisilta saamaansa tietoon. Selviytymiskokemuksen kartoittamiseksi potilaat kirjoittivat päiväkirjoja kuuden kuukauden ajan, ja heidät haastateltiin 18 kuukautta sydäninfarktin jälkeen. Depressio-oireista kärsivien potilaiden määrä väheni enemmän interventioryhmässä kuin kontrolliryhmässä, jossa se pysyi korkeana koko seurannan ajan. Alle 60-vuotiaiden interventiopotilaiden rasittuneisuus väheni enemmän kuin kontrolliryhmässä, mutta koeja kontrolliryhmän välinen ero ei ollut merkitsevä. Terveyteen liittyvän elämänlaadun muutoksissa ei seurannan aikana havaittu ryhmienvälistä eroa. Kuitenkin alle 60-vuotiailla terveyteen liittyvä elämänlaatu parani enemmän interventioryhmässä kuin kontrolliryhmässä. Seurannan aikana interventiopotilaiden sekä interventiopotilaiden, joilla ei ollut muita pitkäaikaissairauksia, tarve somaattiseen erikoissairaanhoitoon osittain jopa väheni. Potilaiden kokemuksissa havaittiin pääkategoriat: kliininen ja fyysinen, psykologinen, sosiaalinen, toiminnallinen ja ammatillinen. Pääkategoriat koostuivat alakategorioista, joihin kuului paljon selviytymisessä tukevia ja estäviä tekijöitä. Tyytyväisyys ammattilaisilta saatuun tietoon ei vaihdellut ryhmittäin. Lyhytkestoinen ja helposti opittava interventio, johon potilaat ovat tyytyväisiä, näyttää vähentävän depressio-oireita sydäninfarktin jälkeen. Interpersonal counselling -interventio vaikuttaa olevan hyödyllinen erityisesti nuoremmille potilaille. Tulokset osoittavat, että depressioseulonta ja interpersonal counselling -interventio saattaisi olla hyödyllistä ottaa osaksi rutiinihoitoa sydäninfarktin jälkeen. Alustava selvitys terveyspalvelujen käytöstä on mielenkiintoinen ja osoittaa, että jatkotutkimuksia tarvitaan. Selviytyminen sydäninfarktin jälkeen näyttää koostuvan lukuisista tukevista ja estävistä tekijöistä yksittäisen potilaan omasta näkökulmasta, mikä on hyvä huomioida kehitettäessä käytännön hoitotyötä. Tulokset interpersonal counselling –interventiosta ja potilaan kokemasta selviytymisestä sydäninfarktin jälkeen ovat tuottaneet jatkotutkimusaiheita. Lisäksi tulokset rohkaisevat laajentamaan tutkimusnäkökulmaa sairaanhoidon hallintoon ja koulutukseen.